Analisis Implementasi Pemberdayaan Masyarakat dan Pengaruhnya terhadap Pencegahan Gizi Buruk Bagi Balita Desa Paya Tukai - Noeroel arham; Adella Safitry; Rismaliza Rismaliza; Hizqia Azzura; Ainul Riski; Sayyida Nabila; Widia Rahmatun Anja (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the implementation of community empowerment and its influence on participation in preventing malnutrition in toddlers in Paya Tukai Village. Using mixed methods, data were obtained from in-depth interviews with five informants and a survey of 95 respondents. The results showed that 76.8% of the community considered community empowerment ineffective, even though there was support from the local government. Logistic regression analysis revealed that community empowerment was the most influential factor on community participation in preventing malnutrition (OR: 4.439; p=0.005). Therefore, it is necessary to increase advocacy, strengthen nutrition cadres, and utilize social media for more effective nutrition education.